Cancer cell bioenergetics in response to anti-cancer agents - Geoghegan, Fintan (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2015)
Altered metabolism is a hallmark of cancer (Hanahan and Weinberg, 2011) and while genetic and molecular modifications have enabled cancers to survive the onslaught of various cancer therapies (Pillai et al., 2010), changes in tumour cell metabolism is becoming increasing more important. Neuroblastoma is a malignancy that arises from the neural crest cells of the sympathetic nervous system which accounts for 15% of paediatric cancer deaths remains a difficult cancer to treat. Phenformin, a member of a class of drug called the biguanides which was used to treat type II diabetes has recently been shown to be efficacious in cancer treatment. In the first part of my study the effects of the potentially novel anti-neoplastic drug, phenformin on the metabolism of neuroblastoma SH-SY5Y cells was examined. The potency of phenformin was assessed by the alamar blue assay, propidium iodide incorporation and annexin V staining by flow cytometry. The effect on the bioenergetics of the cell was analysed by the oxygraph respirometer and seahorse extracellular flux analyser. The effect on reactive oxygen species production levels was assessed by dihydro-fluorescein diacetate staining and flow cytometry. The effect of phenformin on energy status was assessed by AMPKinase and acetylCoA carboxylase activation as determined by western blotting. Phenformin proved effective in reducing the cell viability of the neuroblastoma SH-SY5Y cancer cells, causing G1 cell cycle arrest at sub-cytotoxic concentrations and higher concentrations resulted in the neuroblastoma cells undergoing apoptosis. Bioenergetic analysis showed that phenformin significantly decreased oxygen consumption in a dose and time dependent manner by inhibiting complex I of the mitochondria. As a result of this inhibition, endogenous reactive oxygen species production is significantly decreased and AMPKinase and acetylCoA carboxylase become activated due to phenformin treatment of SH-SY5Y cells. Cisplatin is one of the most potent chemotherapeutic drugs used clinic to treat solid cancers (Andrews and Howell, 1990) Cisplatin often yields modest and temporary clinical effects but its usefulness is limited by the acquisition of resistance, leading to drug relapse and therapeutic failure (Johansson et al., 2009, Michels et al., 2013, Locasale, 2012). Resistance can arise through a multitude of mechanisms including decreased drug accumulation, alterations in drug metabolism and mutations of drug targets (Longley and Johnston, 2005, Gottesman et al., 2002). One approach to possibly uncover the root cause of cisplatin resistance is to investigate the metabolic differences of the sensitive and cisplatin resistance cancer cells. In the second part of my study I set out to determine the metabolic changes behind acquired cisplatin resistance in the non small cell lung cancer cell line, H1299 and a mesothelioma cancer cell line, P31. Cell surface marker expression was assessed by flow cytometry. Analysis of the bioenergetic differences between the parental sensitive cell line and resistant sub-line was determined by the seahorse extracellular flux analyser. Determination of mitochondrial abundance was assessed by the citrate synthase assay. The effect on reactive oxygen species production levels was assessed by dihydro-fluorescein diacetate staining and flow cytometry. The effect of acquired cisplatin resistance on mitochondrial biogenesis was assessed assaying key components of the mitochondrial biogenesis pathway, namely sirtuin-1 (SIRT1), sirtuin-3 (SIRT3), transcription factor A, mitochondrial (TFAM) and peroxisome-proliferator activator receptor-γ co-activator 1-alpha (PGC1α) expression as determined by western blotting. It was found that the acquired resistant cell lines demonstrate reduced mitochondrial oxygen consumption rates, reduced mitochondrial abundance and reduced sirtuin-1 (SIRT1), sirtuin-3 (SIRT3), transcription factor A, mitochondrial (TFAM) and peroxisome-proliferator activator receptor-γ co-activator 1-alpha (PGC1α) expression when compared to their cisplatin sensitive cell counterparts. A correlation between increased globotriasylceramide (Gb3) and the acquisition of cisplatin resistance in the H1299 and P31 cells was demonstrated. The expression of the ABC transporters, ABCE1 and ABCB6 were increased in the cisplatin resistant H1299 and P31 cells respectively in comparison to their sensitive cell counterparts. Using the aforementioned knowledge on mechanism, we set out to determine whether we could reverse the attenuation of mitochondrial function, abundance and biogenesis in H1299 cisplatin resistant cells. . To that end we were able to demonstrate that resveratrol treatment, increased mitochondrial reserve capacity, increased mitochondrial abundance and mitochondrial biogenesis in the H1299 cisplatin resistant cells. Similarly SIRT3 over-expression increased mitochondrial oxygen consumption, increased mitochondrial abundance and mitochondrial biogenesis in both the sensitive and resistant H1299 cells. In conclusion, the first part of this work demonstrated that phenformin shows promise as an anti-cancer agent to treat neuroblastoma. The second part highlighted the metabolic differences between cisplatin sensitive and cisplatin resistant non small cell lung cancer and mesothelioma cancer cell lines and the possible utility of resveratrol or SIRT3 over-expression as potential metabolic switches for cancer treatment.
Keywords: Biochemstry, Ph.D.; Ph.D. Trinity College Dublin.